ENHANCING PRONUNCIATION SKILLS IN EFL STUDENTS THROUGH THE ELSA SPEAK APPLICATION - Suci Permatasari; Yani Lubis (Indonesian EFL Journal, 2024)
This study investigates the effectiveness of the ELSA Speak application in improving the pronunciation skills of EFL students. Utilizing a quasi-experimental design, the study compared the pronunciation skills of students using ELSA Speak with those using the U-Dictionary application. Data were collected through pre-tests and post-tests, and analyzed using paired sample t-tests. The researcher employed a paired sample t-test to determine if there was a statistically significant disparity between the pre-test and post-test scores of students' pronunciation abilities following the utilization of the ELSA Speak App in the experimental class and u-dictionary in the control class. The results indicate that students using ELSA Speak showed significant improvement in pronunciation skills compared to those using U-Dictionary. These findings suggest that ELSA Speak is an effective tool for enhancing pronunciation skills in EFL contexts, providing valuable insights for educators and curriculum developers.Keywords: graphic novels; comprehension; reading; values